The Institute of Accounts : nineteenth-century origins of accounting professionalism in the United States - Loeb, Stephen E.; Miranti, Paul J. (London ; New York : Routledge, 2004)
This book focuses upon the Institute of Accounts (IA), an organization to which the modern United States accounting profession can trace its roots. The IA was organized in the early 1880s in New York City and, as discussed in this book, attracted a diverse membership that included some of the leading accounting thinkers of the period. The Institute of Accounts describes the association's early development, its usefulness to the needs of bookkeepers and accountants in the late nineteenth century, and its historical importance.
Origins, goals, and membership, and professional characteristics -- Functionality of the IA and its role in professionalization -- The structure of accounting knowledge and the natural order of society -- Decline of the IA -- Legacy.
Includes bibliographical references (pages 68-102) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Institute of Accounts; Institute of Accounts; Institute of Accounts; Accountants -- United States; Accountants -- Professional ethics -- United States; Comptables -- États-Unis.; Comptables -- Déontologie -- États-Unis.; BUSINESS & ECONOMICS -- Accounting -- Financial; Accountants -- United States; Accountants -- Professional ethics -- United States; Accountants; Accountants -- Professional ethics; United States; Einnahmen- und Ausgabenrechnung; Buchführung; Wirtschaftsprüfer; Ethik; USA